Effects of random disturbances on the stability of a temporally evolving incompressible plane wake. (January 2020) - Jacob, Bruno; Ribeiro Duarte, Lucas Eduardo; Andrade, João Rodrigo; Ribeiro Duarte, Carlos Antonio
Highlights: Direct Numerical Simulation and Large-Eddy Simulation were performed. Temporally evolving incompressible plane wake are investigated. The Random-Flow-Generator (RFG) technique was used to generate turbulence. The invariants of the velocity gradient tensor were evaluated for different perturbations. Differences in local flow strain and topological characteristics of the dissipation of kinetic energy were evaluated. Graphical abstract: Abstract: Direct Numerical Simulations (DNS) and Large Eddy Simulations (LES) of a three-dimensional, temporally evolving incompressible plane wake are performed, seeking to evidence differences in stability, transition and onset of both coherent and fine-scale structures arisen from random perturbations of different amplitudes. The perturbations are generated by the Random-Flow-Generator (RFG) technique, being imposed in the flow as initial conditions. The Navier-Stokes equations are solved in a prismatic domain with periodic boundary conditions in all directions, using a Fourier pseudospectral method. The invariants of the velocity gradient tensor were evaluated for cases with wakes subjected to random perturbations of amplitude 10 − 3, 10 − 4 and 10 − 5 . Moreover, maps of the second and third invariants of the rate-of-strain tensor were analyzed, seeking to evidence the differences in local flow strain and topological characteristics of the dissipation of kinetic energy. In order to assess the fine-scale structures, isosurface plots of the Q -criterion, as well as vorticity contours were used, allowing visual identification of the coherent structures and confirming patterns predicted by the invariant maps. It was found that the characteristic teardrop correlation map is well defined for higher disturbance amplitudes. Based on the analysis of the simulation results, it can be concluded that the fluid element topology allowed a comparative study of the effects of perturbation amplitude on pairing mechanisms.